A changing demographic – Ten years of HIV care. (January 2022) - Nurdin, Nadra; Quirke, Siobhan; Kerr, Colm; Allen, Niamh; O'Halloran, Jane; Moynan, David; O'Doherty, Laura; Grant, Conor; Townsend, Liam; Bergin, Colm
We aimed to benchmark the quality of care and describe characteristics of patients newly attending the HIV clinic at differing time points over the past 10 years, against the Infectious Disease Society of America HIV/AIDS performance measures. We performed a retrospective analysis of records for patients newly attending the HIV clinic in 2011, 2016 and 2018. There was an increase in male attendees in 2018 and 2016 compared to 2011 (88%, 88% vs. 59% p < .001), viral suppression rates were 97%, 83% and 99% ( p < .001), respectively. We observed an increase in patients of South American origin over time. Acquisition risk changed, with increased proportion of MSM (24% in 2011 vs 78% in 2018, p < .001), lower rates of heterosexual (20% in 2018 vs 48% in 2011, p < .001) and IDU transmission (1.5% in 2018 vs 24% in 2011, p < .001). There were lower rates of Chlamydia trachomatis and Neisseria gonorrhoeae testing in 2018 (72%, p < .001), compared to 2016 (84%) and 2011 (83%). Hepatitis B virus vaccination and pneumococcal vaccine rates are declining ( p < .001). We demonstrate the changes in both ethnicity and risk of acquisition over time, high rates of antiretroviral therapy prescription and viral suppression, and highlight the importance of health prevention with sexual health screening and vaccination in this population.